2009
DOI: 10.1037/a0015963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of voucher-based intervention on abstinence and retention in an outpatient treatment for cocaine addiction: A randomized controlled trial.

Abstract: The aims of this study were to assess whether voucher magnitude improved cocaine abstinence and retention in an outpatient treatment for cocaine dependence, and to determine the effectiveness of a contingency management intervention in a European cultural context. A randomized controlled trial was conducted in which 96 participants who were randomly assigned to 1 of 3 treatment conditions in a community setting: standard outpatient treatment, community reinforcement approach (CRA) plus low monetary value vouch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 25 publications
6
29
0
Order By: Relevance
“…Further research in more severe, alcohol-dependent populations should be conducted to determine the feasibility of using transdermal alcohol monitors. However, contingency management is a powerful technique that has been shown to be effective in opiate- and stimulant-dependent (e.g., Aklin et al, 2014; Chutuape et al, 1999; Garcia-Rodriguez et al, 2009; Higgins et al, 1991; Hser et al, 2011; Rogers et al, 2008) populations; this indirectly suggests that it also should work for alcohol dependence. Another limitation of this study is that participants were not randomized to control and treatment groups and our only control comparison was to the prior baseline phase (i.e., Observation Phase) where no contingency was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Further research in more severe, alcohol-dependent populations should be conducted to determine the feasibility of using transdermal alcohol monitors. However, contingency management is a powerful technique that has been shown to be effective in opiate- and stimulant-dependent (e.g., Aklin et al, 2014; Chutuape et al, 1999; Garcia-Rodriguez et al, 2009; Higgins et al, 1991; Hser et al, 2011; Rogers et al, 2008) populations; this indirectly suggests that it also should work for alcohol dependence. Another limitation of this study is that participants were not randomized to control and treatment groups and our only control comparison was to the prior baseline phase (i.e., Observation Phase) where no contingency was applied.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of another study was to analyze the effect of two reinforcement magnitudes on cocaine abstinence and retention in an outpatient treatment for cocaine addiction (Garcia-Rodriguez et al, 2009). The results showed that the two voucher groups obtained better results than the standard care treatment group.…”
Section: Cocaine Dependencementioning
confidence: 99%
“…Over the last twenty years, a behavioral treatment known as contingency management (CM) has been widely studied in the United States (Higgins et al, 1991; Higgins, Wong, Badger, Ogden, & Dantona, 2000; Petry et al, 2005; McDonnell et al, 2013; Petry & Carroll, 2013), recent trials having also been conducted in Spain (Garcia-Rodriguez et al, 2011, 2009; Secades-Villa et al, 2013, 2011), Switzerland (Petitjean et al, 2014), the United Kingdom (Weaver et al 2014) and China (Chen et al, 2013; Jiang et al, 2012). Various meta-analyses and review articles have presented consistent, robust evidence that, when applied alone or in combination with psychosocial or pharmacological treatment, CM is among the most effective treatments with regard to retention in treatment and promoting continuous abstinence from the use of cocaine and other stimulants (Prendergast, Podus, Finney, Greenwell, & Roll, 2006; Lussier, Heil, Mongeon, Badger, & Higgins, 2006; Dutra et al, 2008; Miguel, Yamauchi, Simões, da Silva, & Laranjeira, 2015).…”
Section: Introductionmentioning
confidence: 99%